Studying influences of socio-economic contexts and spatial effects on educational careers - Hillmert, Steffen [Verfasser]; Hartung, Andreas [Verfasser]; Weßling, Katarina [Verfasser] (My University, 2023)
„Socio-economic contexts and spatial effects have received increasing attention at the intersection of sociology and education. This research group has laid substantial groundwork in this emerging field of research by developing concepts and methodological techniques for analysing spatial contexts, by collecting and preparing relevant contextual data that can be linked with survey data, and by measuring the impact of socio-structural contextual characteristics on educational aspirations and chances of transition from school to vocational and academic training. For at least this specific stage in educational careers, the end of secondary schooling, we have been able to demonstrate that socio-spatial contextual settings (neighbourhoods and regional contexts) are relevant for educational inequalities. Our research has also demonstrated that the relation between socio-economic contexts and inequalities in education is complex. In particular, little is known about the temporal, spatial, and interpersonal variation in contextual effects. This chapter provides an overview of analytical concepts, measurements, and empirical findings that relate socio-spatial context conditions to educational outcomes, and it outlines promising avenues of future research.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 1.3.2 Bildungsverhalten und -verläufe; G 1.3.2.2 Übergänge; 370; 300; Bildungsverhalten; Bildungsentscheidung; Berufseinmündung; Einflussfaktor; Sozialökonomie; Regionale Faktoren